People with high HIV viral load within risk networks: who are these people and who refers them best? - Anna Korobchuk; Hayk Davtyan; Olga Denisiuk; Rony Zachariah; Georgios K Nikolopoulos; Dimitrios Paraskevis; Britt Skaathun; John Schneider; Tetyana I Vasylyeva; Leslie D Williams; Pavlo Smyrnov; Samuel R Friedman (Journal of Infection in Developing Countries)
Introduction: Viral load is one of the most important determinants for HIV transmission. Identification of people with high viral load (PHVL) can be effective in limiting onward HIV transmission. In order to improve the identification of these individuals within risk networks, we determined a) the number of PHVL recruited through risk networks b) their socio-demographic, behavioural and clinical characteristics and c) the characteristics of individuals who referred these PHVL to the study.